POLEMIK EPISTEMOLOGI PANCASILA DAN DEMOKRASI YANG KONSTRUKTIF BESERTA IMPLEMENTASINYA - Agustinus Edward Tasma; Heru Santoso (Universitas Negeri Yogyakarta, 2006)
As cristalization values of Indonesion basics, Pancasila has reflections of our self of Nations. Pancasila has representation of everything differents in Nusantara Islands. With Pancasila it can be used on missions for our governents. In Indonesian conditions has wached essential of Pancasila as phylosophies groundlach and we have concern of phylosophy as way of live by differents in Indonesian governent.